A Case of Hypophosphatasia Started Enzyme Replacement Therapy Since Babyhood Stage - Tatsuya Akitomo; Noriko Niizato; Ami Kaneki; Masashi Ogawa; Taku Nishimura; Mariko Kametani; Momoko Usuda; Yuko Iwamoto; Chieko Mitsuhata; Ryota Nomura (Children)
Background: Hypophosphatasia (HPP) is an inherited disease caused by low activity of tissue-nonspecific alkaline phosphatase. Dental characteristics include premature loss of primary teeth, enlarged pulp chambers, and enamel hypoplasia. Although enzyme replacement therapy with asfotase alfa was approved in 2015, there are few reports about the dental outcomes of this treatment. Case presentation: A 1-year-old girl referred to our hospital had already lost two primary teeth at the time of her initial visit. She started enzyme replacement therapy 6 days after birth, and genetic analysis later confirmed the diagnosis of HPP. At the age of 4 years and 7 months, 11 primary teeth had been lost, and some of the exfoliated teeth showed inflammatory root resorption or root fracture. There was also a history of abscess formation in a non-carious primary molar. Conclusions: This report suggests that early enzyme replacement therapy may prevent traditional tooth loss in patients with HPP. It also highlights the new challenges posed for dental professionals in providing infection control in large pulp cavities and receding periodontal tissue.